Cost Accounting Practices and Financial Performance of Small and Medium-Sized Enterprises (SMEs) in General Santos City - Estrellan, Gidelyn Faye C.; Guinucud, Marwa A.; Borela, Samantha Marie P.; Obeso, Maria Cristina P. (International Journal of Research in Interdisciplinary Studies, 2026)
Small and medium-sized enterprises (SMEs) are significant drivers of global economic growth. While high-quality accounting information is evident for the entity’s growth, the effect of cost accounting practices on their financial performance requires further research. This study aimed to determine the relationship between cost accounting practices (absorption costing, marginal costing, and standard costing) and financial performance (measured by return on assets and net profit margin) of SMEs in General Santos City. The research study used a quantitative method, grounded on the descriptive correlational design, to investigate the characteristics of the variables as well as their relationship. This study is anchored on Resource Based View Theory (Wenerfelt, 1984; Penrose,1959) which posits that resources can lead to high performance of a company. A sample size of 327 SMEs was determined using Taro Yamane’s Formula (1964). Questionnaires based on a five-point Likert scale were used to collect data, which yielded 151 responses. Analysis of the 151 SMEs responses revealed a high level of both cost accounting practices and financial performance. Furthermore, Spearman correlation coefficient analysis indicated a significant positive relationship between these variables among SMEs in General Santos City. Future research may examine other potential variables that could further weaken or strengthen this relationship.